Sistem Perhitungan Penggajian Pekarya Berbasis Web Di PT. Petrowell Energi - Johandri Iqbal; Refhika Dwi Yanthi (LPPM Politeknik Jambi, 2020)
PT. Petrowell Energi is a company engaged in contracting, trading, repair for industrial equipment and the provision of services for empowering human resources. In providing services, this company processes its data using a computerized but simple payroll system that uses software Ms. Excel, so that in processing data experienced obstacles that cause the process of errors such as incorrect inputting salary data, personal data and salary reports that must be calculated and the process of calculation is repeated from each employee. The purpose of this web-based payroll information system is to overcome the problems that arise in the manual system currently running at PT. Petrowell Energy as well as being a good solution for companies for the creation of a more transparent and accountable system, in its processing it will be more effective and efficient. The method of data collection is done by means of interviews, observations, documentation and analysis of systems used by the company. The results of this study are to produce a computerized payroll information system that is provided with ease in providing payroll data information such as employee data information, and payroll data. In payroll data information systems, the authors use data flow diagrams, DFD, ERD, and MySQL for data processing.